Level of Resistance of S1 Lines of Corn Plants to Drought Stress - Aulia Adeputri, Amanah; Sudika, Wayan; Malik Yakop, Uyek (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
The formation of hybrid varieties by self-crossing the F2 population has been carried out, thus obtaining the first generation selfing line (S1). This research aims to determine the level of drought stress resistance of S1 lines and corn plants and the correlation between their characters and the ISC value for each stress. The method used is an experimental method with field experiments. The experiment was carried out from March to June 2023 at the location in Gumantar Village, Kayangan District, North Lombok Regency. The experimental design used was a randomized block design (RAK) in a split plot design with the main plot consisting of stress and normal treatments, while the sub plots were the S1 lines and the F2 population. The results showed that there were different levels of resistance in the S1 line. G27 has resistance with tolerant criteria, 13 lines are moderately tolerant, and 16 other lines are susceptible; Correlation criteria between characters vary with the ISC value in each stress and normal condition. Characters that are strongly correlated with the ISC value are chlorophyll A, total chlorophyll, harvest dry cob weight, and dry kernel weight. The formation of S2 lines can be done using tolerant and moderately tolerant lines.